PENGARUH STRUKTUR KEPEMILIKAN, ARUS KAS BEBAS, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MELALUI STRUKTUR MODAL - Rachmat Yusuf Kresno Wibowo; Nur Fadjrih Asyik; Suwardi Bambang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
This study aims to examine and to analize the influence of ownership structure (managerial ownership and institutional ownership), free cash flow and firm size on firm value with capital structure as intevening variable. The population used for this research is Property and Real Estate companies listed in Indonesia Stock Exchange (IDX) in 2014-2018. This research using purposive sampling technique for its sampling method, from the total 53 companies we obtained 40 samples companies and 200 samples for 5 years observation periodes. The analytical method that this research used to determine the direct effect is multiple linier regression analysis and to determine its indirrect effect simple mediation (causal steps strategy) is used with the assistance of SPSS version 24.0. The Result of this research found that capital structure couldn’t mediated the effect of managerial ownership, institutional ownership, free cash flow on firm value, but capital structure could mediated the effect of firm size on firm value.